Secondary School Madrasas in Bangladesh : Incidence, Quality, and Implications for Reform - World Bank (Washington, DC, 2014)
This report presents findings from the first ever comprehensive survey to document the incidence and quality of secondary madrasas in Bangladesh. Analysis also draws upon other publicly available administrative and household level datasets. Currently the authors have very little information on school quality in general due to no national learning assessment system and because schools from different streams are tested under different Boards. Thus it is always important to examine the quality of aided madrasas relative to aided secular schools. The report highlights new challenges: while gender equality in access has been achieved in both schools and madrasas, girls remain systematically disadvantaged in terms of learning outcomes. The female learning penalty remain is particularly pronounced in case of madrasas. Overall, the quality of mathematics and English learning is low in madrasas, but performance of students of mainstream schools is also unsatisfactory average quality remains poor across the range of rural institutions. Overall, this report represents an empirically grounded investigation into the hitherto undocumented changes Bangladesh has witnessed in the secondary madrasa school sector in the past two decades. Based on their analysis, the authors suggest a range of policy initiatives that cover the entire secondary education sector, not just the madarasa education. Given the wealth of data collected on secondary institutions and households during the survey, this report only represents the first of a series of rigorous empirical research and analysis which will be undertaken. It is hoped that the report will provide an impetus towards an evidence-based policy debate on madrasas and other critical issues in the education sector.